La hacienda del Marqués de Velada. Perfiles de una economía cortesana, 1561-1616 - Martínez Hernández, Santiago (Cuadernos de Historia Moderna, 2003)
The present paper deals with courtisan nobility economies, based on Velada Marquisate as main object. Our purpose is to offer a general scope about the origin and evolution of this hacienda during the life of second marquis, Gómez Dávila y Toledo (1561-1616). For that matter we have analized his incomes, entrances, charges and the economical consecuencies aroused by the subordination to the Crown.